2014
DOI: 10.3329/bmj.v41i1.18774
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Young Child Feeding Practices upto Two Years of Age and Their Nutritional Status

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
0
10
1
2
Order By: Relevance
“…The most common promoter of good CF at the family level was levels of maternal education, identified in seven studies by Kabir [6,16,23,31,38,39,45]. It is notable that two studies found that children were likely to receive improved CF if they were male [26,37].…”
Section: Promotersmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common promoter of good CF at the family level was levels of maternal education, identified in seven studies by Kabir [6,16,23,31,38,39,45]. It is notable that two studies found that children were likely to receive improved CF if they were male [26,37].…”
Section: Promotersmentioning
confidence: 99%
“…The most commonly identified barriers at the family level were mother with poor education (9 studies [6,21,23,35,36,38,39,45,41]) and lack of knowledge of CF (8 studies [14,24,26,32,35,40,42,46]). It is notable that two studies found that maternal employment was a barrier to good CF [24,36].…”
Section: Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] Better indicators relating to introduction of solid, semi-solid, or soft foods reflect positively for the population under investigation though the same cannot be commented for widely varying numbers receiving complementary feeding at 6-9 months of age (24-71.7%). [19][20][21] Everything else being equal, children fed timely complimentary feeding are expected to be well nourished as evident by studies conducted as far as Malawi and Pakistan. [22,23] Indicators reflecting minimum dietary diversity and minimum meal frequency seem difficult to improve as evident by reported figures that generally range from dismal to just satisfactory.…”
Section: Discussionmentioning
confidence: 99%